The Immigrant-Food Nexus Borders, Labor, and Identity in North America - Agyeman, Julian; Giacalone, Sydney (Food, Health, and the Environment, 2020)
The intersection of food and immigration in North America, from the macroscale of national policy to the microscale of immigrants' lived, daily foodways. This volume considers the intersection of food and immigration at both the macroscale of national policy and the microscale of immigrant foodways-the intimate, daily performances of identity, culture, and community through food. Taken together, the chapters-which range from an account of the militarization of the agricultural borderlands of Yuma, Arizona, to a case study of Food Policy Council in Vancouver, Canada-demonstrate not only that we cannot talk about immigration without talking about food but also that we cannot talk about food without talking about immigration. The book investigates these questions through the construct of the immigrant-food nexus, which encompasses the constantly shifting relationships of food systems, immigration policy, and immigrant foodways. The contributors, many of whom are members of the immigrant communities they study, write from a range of disciplines. Three guiding themes organize the chapters: borders-cultural, physical, and geopolitical; labor, connecting agribusiness and immigrant lived experience; and identity narratives and politics, from "local food" to "dietary acculturation." Contributors Julian Agyeman, Alison Hope Alkon, Fernando J. Bosco, Kimberley Curtis, Katherine Dentzman, Colin Dring, Sydney Giacalone, Phoebe Godfrey, Sarah D. Huang, Maryam Khojasteh, Jillian Linton, Pascale Joassart-Marcelli, Samuel C. H. Mindes, Laura-Anne Minkoff-Zern, Christopher Neubert, Fabiola Ortiz Valdez, Victoria Ostenso, Catarina Passidomo, Mary Beth Schmid, Sea Sloat, Dianisi Torres, Kat Vang, Hannah Wittman, Sarah Wood